Implementation of Web-Based Virtual Laboratory Media in Learning - Puspita Ratna Susilawati (Jurnal Taman Vokasi, 2019)
The integration of information and communication technology in learning through the application of virtual laboratory media can be an alternative solution to overcome the constraints of time, cost, and laboratory safety in biology labs. Virtual laboratories are very suitable to be applied to the mechanism of evolution because they involve the context of space and time, and can provide opportunities for students to learn independently and increase active student involvement in learning. These study aims are to determine the effect of the application of virtual laboratory media on the understanding of student concepts; knowing increasing students' understanding of the concept of evolutionary mechanisms, and knowing students' responses after learning with virtual laboratories.This type of research is a pre-experimental design (nondesign) with one group pretest-posttest design. The research subjects were 37 students. The media used as many as 8 web-based virtual laboratory programs (online) that can be freely accessed. Data collection techniques include tests (pretest and posttest) and questionnaires. The pretest and posttest values were analyzed by the T-test while the questionnaire data were analyzed descriptively. The application of web-based virtual laboratory media on the evolution mechanism material influences the understanding of student concepts (t arithmetic> t table then H0 is rejected and H1 is accepted) The application of these media increases students' understanding of the concept of evolutionary mechanisms. The mean value increased from pretest 23.65 to 56.08 at the posttest with an increase of 32.43. Student responses to the application of media in learning showed 91.89% of students felt helped in understanding the process of evolution while 100% of students felt helped in understanding the role of evolution in causing evolution.